(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is one of the countries that takes pride in its rich and unique cultural heritage and traditions. The country has indigenous traditional healing systems like Yoga and Ayurveda, their recognition can be ascertained from the fact that western countries have also accepted these India gifts, furthermore, these have also been scientifically endorsed for their effectiveness in curing certain ailments. Music therapy is the latest to join the spectrum of Indian traditional system of healthcare and healing.